A new species and new records of the genus Bolboceras Kirby, 1819 (Coleoptera: Scarabaeoidea: Geotrupidae: Bolboceratinae) from India - Gupta, Devanshu; Chandra, Kailash; Ghosh, Joyjit; Das, Priyanka (Zootaxa, 2020)
A new species of the genus Bolboceras Kirby, 1819; Bolboceras arunachalensis Chandra, Gupta & Ghosh, new species (Coleoptera: Geotrupidae: Bolboceratinae) from Arunachal Pradesh, India is described, diagnosed, and illustrated. Bolboceras perpunctatum Krikken, 2013 is recorded for the first time from Central India.